Entrepreneurship, structural change and a global economic crisis - Thomas Gries; Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Building on a Lewis-type model of structural change and entrepreneurship we show how a global economic crisis consisting of a financial and a trade shock can undermine structural change in developing countries via the start-up and innovation activities of entrepreneurs. The model analytics identifies a number of challenges for structural change in a post-crisis world, including dealing with greater bank concentration, higher costs of bank monitoring and stricter regulations and collateral requirements, flights-to-safety in global finance and reduced incentives for innovation and job-creating start-up activities.
Keywords: M13; O10; O14; L26; 330; entrepreneurship; global economic crisis; structural change